2021
DOI: 10.3390/cancers13112621
|View full text |Cite
|
Sign up to set email alerts
|

The Endless Sources of Hepatocellular Carcinoma Heterogeneity

Abstract: Hepatocellular carcinoma (HCC) represents a global health problem. The incidence keeps increasing and current therapeutic options confer limited benefits to the patients. Tumor heterogeneity plays a central role in this context, limiting the availability of predictive biomarkers and complicating the criteria used to choose the most suitable therapeutic option. HCC heterogeneity occurs at different levels: within the population (inter-patient heterogeneity) and within tumors from the same patient (intra-patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 114 publications
0
19
0
Order By: Relevance
“… 12–15 Unfortunately, due to the complexity of immunotherapy and the genetic heterogeneity, this method took effect only for partial patients. 16 Emerging evidence demonstrated that the change of tumor-induced immune infiltrate cells was a momentous mechanism that carcinomas develop to evade immune surveillance. Meanwhile, tumor immune infiltration carries a clinicopathological significance in predicting prognosis and therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“… 12–15 Unfortunately, due to the complexity of immunotherapy and the genetic heterogeneity, this method took effect only for partial patients. 16 Emerging evidence demonstrated that the change of tumor-induced immune infiltrate cells was a momentous mechanism that carcinomas develop to evade immune surveillance. Meanwhile, tumor immune infiltration carries a clinicopathological significance in predicting prognosis and therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of hepatocellular carcinoma (HCC) is highly diverse and includes factors such as Hepatitis B and C, exposure to environmental toxicants, NAFLD, MetS, cigarette smoking, and ALD [173]. This heterogeneity makes treating HCC a significant challenge, leading to over 800,000 deaths worldwide each year [173]. The prognosis for HCC patients is poor (five-year survival rate less than 20%) and its diagnosis is rising in the United States [174][175][176].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Similar to muscle cells, most cancer cells are metabolically flexible. The different quantitative contributions of mitochondria to cellular bioenergetics, together with genomic instability and differences in the microenvironment, are important determinants of tumor heterogeneity (Kuipers et al, 2017;Barcena-Varela and Lujambio, 2021;Wei et al, 2021). Tumor metabolic heterogeneity is increasingly recognized as a factor causing failures in cancer treatment (Gentric et al, 2017;Kim and DeBerardinis, 2019).…”
Section: Mitochondria Tumor Metabolic Flexibility and Tumor Heterogeneitymentioning
confidence: 99%